Balantidium coli causing acute diarrheal disease in a diabetic - Bose, Sharan; Sai, Sooraj; K. V., Rajalakshmi; Y., Dayanandan; Dorairaj, Aruna (International Journal of Advances in Medicine, 2023)
Balantidium coli is a rare, free-living protozoan causing an acute diarrheal disease in human beings similar to amoebic dysentery. It is found in tropical and subtropical regions but is very rare in the Indian subcontinent. It is an exceedingly rare infection and only a handful of case reports have been published worldwide on this infection. Here, we report a case of a Balantidium coli infection presenting as an acute diarrheal disease from South India.